2021
DOI: 10.1002/ejsp.2742
|View full text |Cite
|
Sign up to set email alerts
|

The trickle‐down effect of procedural fairness on perceptions of daily discrimination: How societal actors can build social trust among minority members

Abstract: The present research investigated the trickle‐down effect of procedural fairness enacted by societal institutions on minority members’ social trust. Building on the racial identity development hypothesis, we argued that procedural fairness represents a racial socialization experience, which influences how minorities perceive discrimination in daily life. Perceived group discrimination, in turn, impacts social trust. The results of five studies with African American samples corroborated the hypothesized mediati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 78 publications
1
15
0
Order By: Relevance
“…Along similar lines, Dierckx et al. (2020; Experiment 1) demonstrated that priming participants with unfairness (and thus immorality) increased their attributions to discrimination when they witnessed a fellow minority group member being rejected by a White individual. Moreover, literature on selection and promotion in organisational contexts has shown that candidates are more likely to attribute a negative outcome to discrimination when it is preceded by an unfair (and thus immoral) selection procedure (Bies & Shapiro, 1988; Harris et al., 2004).…”
Section: Introductionmentioning
confidence: 78%
“…Along similar lines, Dierckx et al. (2020; Experiment 1) demonstrated that priming participants with unfairness (and thus immorality) increased their attributions to discrimination when they witnessed a fellow minority group member being rejected by a White individual. Moreover, literature on selection and promotion in organisational contexts has shown that candidates are more likely to attribute a negative outcome to discrimination when it is preceded by an unfair (and thus immoral) selection procedure (Bies & Shapiro, 1988; Harris et al., 2004).…”
Section: Introductionmentioning
confidence: 78%
“…A study in Latin America suggested that distributive unfairness and income inequality are associated with lower levels of political trust ( Zmerli and Castillo, 2015 ). Because procedural fairness is of great importance to the survival of vulnerable groups ( Dierckx et al, 2021 ). Ziller (2017) also found that institutional fairness can ensure the fairness of rights and interests by narrowing the gaps between different groups, which improved social integration and tolerance as well as social trust.…”
Section: Discussionmentioning
confidence: 99%
“…Positive human behaviors are more likely to be inspired in the fair surrounding, such as trust and trustworthiness ( Lind, 2001 ; Jones and Martens, 2009 ). The result may be because the sense of fairness could lead people to lower their vigilance and treat others equally, it prevents discrimination, prejudice, and conflict in society ( Dierckx et al, 2021 ). This benefits to building a harmonious society and interpersonal trust and institutional trust.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For special groups, procedural fairness is of great significance to their survival. Social trust is able to be improved because fairness can reduce discrimination and prejudice and make them feel social tolerance (Dierckx et al, 2021). Zhang and Zhou (2018) found that social justice has a statistically positive impact on social trust, regardless of distributive or procedural justice.…”
Section: Social Fairness and Social Trustmentioning
confidence: 99%